Pengaruh Personal Values Terhadap Job Satisfaction Dimediasi Oleh Komunikasi Interpersonal - Urip Darmawan; Agus Seswandi; Burhan Burhan (New Economy, 2025)
The purpose of this study was to determine the Analysis of the Influence of Personal Value on Job Satisfaction of Employees of the Housing, Settlement and Land Service of Bengkalis Regency mediated by Interpersonal Communication The population in this study were all ASN employees of the Housing, Settlement and Land Service of Bengkalis Regency totaling 55 people where the sampling was carried out using the saturated sample method. The data collection technique used a questionnaire and distribution using a google form. The data analysis technique in this study was with Structural Equation Modeling (SEM) using SmartPLS 3.0 as a data processing tool. The results of this study indicate that Personal Values ​​and personal communication have a positive effect on employee Job Satisfaction, Personal Values ​​have a positive effect on employee interpersonal communication, and Personal Values ​​have a positive effect on employee Job Satisfaction mediated by interpersonal communication